The impact of trade openness on the growth of the industrial sector in Algeria - Oukkal, Antar (Finance and Business Economies Review, 2022)
The study aims to test the relationship between the trade openness and the growth of industrial sector During the period (1990-2019), we used the latest statistical methods have been modern in time series of estimation of the unrestricted regression error correction model (autoregressive Distribution lag (ARDL), Using the statistical program (EVIEWS-10). The study concludes that There is an inverse relationship between trade openness and the growth of the industrial sector, and it’s no statistical significance, the technological and technical flows bear won't have any positive impact if it won't lead to the expansion of exports and this what is noticed in the Algerian economy as more than 95% of its exports are oil. The study also recommended directing the financial resources derived from the foreign trade sector and foreign direct investments towards the industrial sector to raise its productivity, especially the industrial sector outside of hydrocarbons